2023
DOI: 10.1002/adbi.202300173
|View full text |Cite
|
Sign up to set email alerts
|

Modes and Mechanisms of Salivary Gland Epithelial Cell Death in Sjogren's Syndrome

Abstract: Sjogren's syndrome is an autoimmune disease in middle and old‐aged women with a dry mucosal surface, which is caused by the dysfunction of secretory glands, such as the oral cavity, eyeballs, and pharynx. Pathologically, Sjogren's syndrome are characterized by lymphocyte infiltration into the exocrine glands and epithelial cell destruction caused by autoantibodies Ro/SSA and La/SSB. At present, the exact pathogenesis of Sjogren's syndrome is unclear. Evidence suggests epithelial cell death and the subsequent d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 141 publications
0
1
0
Order By: Relevance
“…Aberrant DNA methylation has also been implicated in non-immune cells. Considering that SGECs play an essential function in the emergence of SjS ( 140 ), it has been found that SGECs also play a significant function in the immune regulation in the pathophysiology of SjS and influencing the initiation and continuation of autoimmune response and inflammation ( 7 , 141 , 142 ). As SjS advances, the fundamental variations in the proteome of SGECs between SjS and healthy controls provide tangible evidence of SGEC transformation into an innate immune cell ( 143 ).…”
Section: Association Of Salivary Gland Epithelial Cells With Dna Meth...mentioning
confidence: 99%
“…Aberrant DNA methylation has also been implicated in non-immune cells. Considering that SGECs play an essential function in the emergence of SjS ( 140 ), it has been found that SGECs also play a significant function in the immune regulation in the pathophysiology of SjS and influencing the initiation and continuation of autoimmune response and inflammation ( 7 , 141 , 142 ). As SjS advances, the fundamental variations in the proteome of SGECs between SjS and healthy controls provide tangible evidence of SGEC transformation into an innate immune cell ( 143 ).…”
Section: Association Of Salivary Gland Epithelial Cells With Dna Meth...mentioning
confidence: 99%